Characterization of polysaccharide from Pleurotus eryngii during simulated gastrointestinal digestion and fermentation. (15th February 2022) - Ma, Gaoxing; Xu, Qian; Du, Hengjun; Muinde Kimatu, Benard; Su, Anxiang; Yang, Wenjian; Hu, Qiuhui; Xiao, Hang
Highlights: PEP is not digested during simulated digestion. PEP is degraded and utilized by intestinal flora. PEP leads to significant increases in SCFAs, especially acetic acid and propionic acid. The relative abundance of Firmicutes increased significantly. Abstract: Pleurotus eryngii is a valuable new edible mushroom variety cultivated on a large scale in China. The polysaccharides found in this mushroom are strong bioactive. This study used simulated digestion and fermentation model to study the digestion and fermentation characteristics of Pleurotus eryngii polysaccharide (PEP) and its effect on gut microbiota. The results showed that the molecular weight of PEP remained unchanged after simulated digestion, and the overall structure of PEP was not destroyed, indicating that PEP was not decomposed during digestion. However, during fermentation, PEP was degraded and utilized by intestinal flora to produce a variety of short-chain fatty acids (SCFAs), which reduced the pH value in fecal cultures. Meanwhile, PEP regulated the composition of intestinal flora, and the relative abundance of Firmicutes increased significantly. These suggests that PEP can be used as a functional food to promote intestinal health and prevent disease.